Somatostatin receptor-targeted polymeric nanoplatform for efficient CRISPR/Cas9 gene editing to enhance synergistic hepatocellular carcinoma therapy - Suqin Zhang; Meng Li; Jingyi Zeng; Songli Zhou; Feifan Yue; Zhaoyi Chen; Lixin Ma; Yang Wang; Fei Wang; Jingwen Luo (Journal of Nanobiotechnology)
Abstract Introduction The CRISPR/Cas9 system-based gene therapy can fundamentally address the issues of cancer occurrence, development, progression, and metastasis. However, the lack of targeting and effectiveness hinders gene therapy from entering clinical application. Herein, a somatostatin receptor-targeted polymeric nanoplatform is developed for the delivery of a PD-L1-targeted CRISPR/Cas9 system and synergistic treatment of hepatocellular carcinoma. This nanoplatform can effectively incorporate the CRISPR/Cas9 system and the chemotherapeutic drug paclitaxel to simultaneously address the biological safety and packaging capacity issues of viral vectors. After the octreotide-modified polymer (LNA-PEG-OCT) guided the nanoparticle into hepatoma carcinoma cells, the nanoparticle protected the CRISPR/Cas9 ribonucleoprotein complex (RNP) and achieved lysosomal escape. Then, the RNP reached the target gene (PD-L1) under the guidance of the single guide RNA (sgRNA) in the RNP. The PD-L1 gene editing efficiency reached up to 55.8% for HepG2 cells in vitro and 46.0% for tumor tissues in vivo, leading to effective suppression of PD-L1 protein expression. Substantial inhibition of hepatocellular carcinoma cell proliferation and further 79.45% growth repression against subcutaneous xenograft tumors were achieved. Overall, this somatostatin receptor-targeted polymeric nanoplatform system not only provides a promising nanocarrier for CRISPR/Cas9 system delivery, but also expands the potential of combining gene editing and chemotherapy. Graphical Abstract